Drifter observations of surface currents in the Cyprus Gyre - Poulain, P.-M.; Menna, M.; Mauri, E.; Pirro, A.; Hayes, D. R.; Gildor, H. (Frontiers in Marine Science, 2023)
Wavelet ridge analysis was applied to the data of drifters caught in the Cyprus Gyre in the eastern Mediterranean Sea to study surface currents at low (rotating circulation) and high (near-inertial motion) frequencies. Drifter observations indicate that the orbital speed is highest at about 30 km from the gyre center (reaching ~45 cm/s) and that the Rossby number in the gyre can be as high as 0.25. Drifters also show that strong near-inertial currents with speed of 35-40 cm/s can exceed the gyre rotation speed and that the background vorticity inside the gyre generally shifts the effective inertial frequency to values smaller than the local inertial frequency. As a result, the near-inertial currents are subinertial and are trapped in the mesoscale vortex. For example, the near-inertial motions in the Cyprus Gyre in June 2017 reached 40 cm/s in its inner core with a red shift of ~0.1 cpd, while on its edge they were limited to 10-20 cm/s, under similar wind forcing. This difference is due to trapping of the near-inertial energy inside the gyre. The observed inertial currents are largely driven by the local wind, especially when the effective inertial frequency becomes diurnal and resonance with wind diurnal variability occurs. A damped slab model of the inertial currents in the mixed layer is only partially successful in simulating the observations.